Association of Pre‐Pregnancy Body Mass Index, Pregnancy‐Related Weight Changes, and Parity With the Risk of Developing Degenerative Musculoskeletal Conditions. Issue 5 (May 2016) - Bliddal, Mette; Pottegård, Anton; Kirkegaard, Helene; Olsen, Jørn; Jørgensen, Jan S.; Sørensen, Thorkild I. A.; Dreyer, Lene; Nohr, Ellen A.
Abstract : Objective: To examine how pre‐pregnancy body mass index (BMI), parity, and pregnancy‐related weight changes are associated with long‐term risk of degenerative musculoskeletal conditions. Methods: A total of 79, 687 mothers with singleton births from the Danish National Birth Cohort were included. Information on height and weight prior to pregnancy and 6 months postpartum as well as gestational weight gain (GWG) was obtained from telephone interviews, while parity was derived from the Danish Medical Birth Registry. Diagnoses of musculoskeletal conditions, including osteoarthritis, disc disorders, low back pain, and soft tissue disorders, were obtained from the Danish National Patient Registry. Hazard ratios (HRs) were estimated using a Cox proportional hazards regression model. Results: The cumulative incidence of musculoskeletal conditions during a median follow‐up of 12.4 years was 19.7%. The risk of musculoskeletal conditions increased with both increasing pre‐pregnancy BMI and increasing parity. Compared to normal‐weight first‐time mothers, the highest risk was seen in obese women with >2 births (HR 1.61 [95% confidence interval 1.41–1.83]). GWG of 10–15 kg was associated with the lowest risk of musculoskeletal conditions. Compared to women with no change in weight from preconception to 6 months after childbirth (±1 BMI unit), increasing postpartum weight increased the risk of musculoskeletal conditions in normal‐weight and overweight women. Conclusion: Our findings indicate that high pre‐pregnancy BMI increases the risk of degenerative musculoskeletal conditions. Low and high GWG, higher postpartum weight retention, and especially higher parity are associated with an increased risk. Prevention of being overweight before, during, and after pregnancy may reduce the risk of development of degenerative musculoskeletal conditions among mothers.